Using neutron radiography to assess water absorption in air entrained mortar. (1st May 2016) - Li, Wenting; Pour-Ghaz, Mohammad; Trtik, Pavel; Wyrzykowski, Mateusz; Münch, Beat; Lura, Pietro; Vontobel, Peter; Lehmann, Eberhard; Weiss, W. Jason
Highlights: The effect of air content on the degree of saturation in mortar is investigated. The effect of initial moisture content on degree of saturation is discussed. Neutron radiography is used to visualize moisture ingress. Insight to water sorption is provided by relating it to pore size distribution. Abstract: Concrete highway and airport pavements are designed to be long lasting; however, some concrete pavements have shown premature deterioration at the cracks and joints. It has been hypothesized that one cause of this deterioration is associated with fluid ingress, especially in cases where those fluids contain deicing salts. This paper examines fluid ingress in mortar using a cross-sectional geometry that is similar to a typical concrete pavement joint. Time-dependent and spatial aspects of fluid ingress are examined using neutron radiography (NR), which was performed using the thermal neutron radiography station at the neutron spallation source at the Paul Scherrer Institut (PSI). Specifically, this paper examines the role of the initial relative humidity (or degree of saturation) and air content on the fluid ingress. The work indicates that the initial fluid ingress reaches a specific degree of saturation relatively rapidly, where the large capillary and gel pores appear to be filled in (commonly referred to as the nick point in sorption tests) and the entrapped and entrained air pores fill in more slowly over time.